Implementasi Praktik Inisiasi Menyusu Dini (IMD) pada Ibu Bersalin terhadap Keberhasilan ASI Eksklusif di Puskesmas Labuan Bajo 2026 - Hardiyanti Fitrah Awaliyah (Journal of Educational Innovation and Public Health, 2026)
Early Initiation of Breastfeeding is the process of breastfeeding a baby immediately after birth, where the baby is allowed to find his mother's nipple by himself, which is done at least one hour immediately after birth. Failure to implement early initiation of breastfeeding can have an impact on increasing the high mortality and morbidity rates. Therefore, an analysis is needed on the implementation of early initiation of breastfeeding practices on the success of Exclusive Breastfeeding. This study aims to explore the experience of implementing early breastfeeding initiation (IMD) practices in mothers in labor towards the success of exclusive breastfeeding at the Labuan Bajo Community Health Center. This research method is qualitative using a phenomenological approach with an exploratory design. Interviews were conducted with 7 informants with data analysis using Collaizi with the stages of transcribing the recording results in verbatim form, assessing the accuracy of the interview results, familiarizing the data, selecting keywords that will be used as subthemes and themes, writing all analysis results in narrative descriptive form from the research results, and rechecking (validating) the informants. The study found that mothers had both positive and negative perceptions regarding the benefits of early breastfeeding. They also received support from their husbands, families, and midwives. The barriers they encountered included access to healthcare facilities and a lack of knowledge about early initiation of breastfeeding. They also hoped that healthcare facilities would hold counseling sessions and classes for pregnant women.